If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28w + -3 = 5w + -0.8 Reorder the terms: -3 + 28w = 5w + -0.8 Reorder the terms: -3 + 28w = -0.8 + 5w Solving -3 + 28w = -0.8 + 5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-5w' to each side of the equation. -3 + 28w + -5w = -0.8 + 5w + -5w Combine like terms: 28w + -5w = 23w -3 + 23w = -0.8 + 5w + -5w Combine like terms: 5w + -5w = 0 -3 + 23w = -0.8 + 0 -3 + 23w = -0.8 Add '3' to each side of the equation. -3 + 3 + 23w = -0.8 + 3 Combine like terms: -3 + 3 = 0 0 + 23w = -0.8 + 3 23w = -0.8 + 3 Combine like terms: -0.8 + 3 = 2.2 23w = 2.2 Divide each side by '23'. w = 0.09565217391 Simplifying w = 0.09565217391
| 12-5x+2x=-8x+37 | | -5+n=1 | | x-37=48 | | (y-4)*2+(y+1)*2=(y-2)*2+(y+6)+3 | | 1.4d=1.4d+9.21 | | (-61)+x=-60 | | 39-6v=-v-4(8v-3) | | -12=10(u-2) | | m^2-2m-21=0 | | 22y=7(3x-6) | | 15/-20 | | -7.17-17.8k=-17.8k-7.17 | | 62+x=84 | | 12.2t+5.93=5.93+12.2t | | -5(x+2)-11=15+4 | | (-96)+x=-55 | | -3j^2+12j+21=0 | | 36-2x=-8(5x+5) | | -12=3(u-2) | | 3x+2(3x-4)=-53 | | -2.04+13.9f+11.87=-1.75+13.9f | | 1/3x-1/2=5 | | 12/4=r/6 | | x-61=30 | | 47+x=-66 | | 8+5r-3=9r+6-3r | | -20c-13=-2-20c-11 | | 24=90n | | 7(6+5n)-7n=-8n+6 | | -3q^2+6q=-123 | | 9x-(4x+6)=2(2x+1) | | -3/4(8-12)=5x-2 |